2021
DOI: 10.1371/journal.pntd.0009274
|View full text |Cite
|
Sign up to set email alerts
|

Findings from the initial Stepwise Approach to Rabies Elimination (SARE) Assessment in China, 2019

Abstract: In 2015, China and other member states of the United Nations adopted the goal of eliminating dog-mediated rabies by 2030. China has made substantial progress in reducing dog-mediated human rabies since peaking with more than 3,300 reported cases in 2007. To further improve coordination and planning, the Chinese Center for Disease Control and Prevention, in collaboration with the United States Centers for Disease Control and Prevention, conducted a Stepwise Approach towards Rabies Elimination (SARE) assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…This is related to the reason of keeping dogs for house guarding ( 10 ). This research also found that only about 19.1% of dog-owning households reported having their dogs vaccinated, much lower than the minimum requirement to achieve interruptions in dog-mediated rabies spread ( 1 ) and also lower than that in economically developed regions, such as 85.0%–100.0% in Shanghai ( 10 ), 80.0% in Beijing ( 11 ), and above 70% in the Pearl River Delta region in Guangdong Province ( 4 ). The findings illustrated that there will still be much room for improving rabies control when progress is achieved in the endemic area ( 12 ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This is related to the reason of keeping dogs for house guarding ( 10 ). This research also found that only about 19.1% of dog-owning households reported having their dogs vaccinated, much lower than the minimum requirement to achieve interruptions in dog-mediated rabies spread ( 1 ) and also lower than that in economically developed regions, such as 85.0%–100.0% in Shanghai ( 10 ), 80.0% in Beijing ( 11 ), and above 70% in the Pearl River Delta region in Guangdong Province ( 4 ). The findings illustrated that there will still be much room for improving rabies control when progress is achieved in the endemic area ( 12 ).…”
Section: Discussionmentioning
confidence: 73%
“…In 2015, the World Health Organization, the World Organisation for Animal Health, and the Food and Agriculture Organization of the United Nations (FAO) in collaboration with Global Alliance for Rabies Control proposed eliminating dog-mediated rabies globally by 2030 ("zero by 2030"). Although the vaccination coverage among registered dogs is required to meet 90% by the National Animal Rabies Prevention and Control Plan (3), current low vaccination coverage in dogs was the main obstacle for China to eliminate dogtransmitted rabies (4). Therefore, it is important to know the impacting factors associated with low dog vaccination rates in rural areas to design well-targeted rabies control programs.…”
mentioning
confidence: 99%
“…OHZDP workshop participants from other countries made similar recommendations for developing systems or mechanisms to organize and harmonize data collection (including standardization) across the relevant different sectors for the priority zoonoses [32]. Such systems could be implemented at the national and provincial level in China and include feedback tools (e.g., dashboards for visualization) for key decision makers in each sector [33,34]. Animal disease surveillance, including at animal farms, breeding sites, and market locations are critical for early detection of zoonotic diseases and limiting transmission or 'spill-over' to the human population.…”
Section: Plos Onementioning
confidence: 99%
“…Efforts to build capacity and improve collection and reporting of surveillance data include regional and national level training on reliable laboratory methods [42] and the use of electronic surveillance platforms [48]. A few articles report countries' self-assessments using the Stepwise Approach towards Rabies Elimination (SARE) tool [126], for example, Haiti, Kenya, and Liberia have used their SARE score for effective advocacy [117,127]. Despite data limitations, results from these assessments indicate most countries in Africa are in early stages of SARE, whereas some countries in Asia are further progressed [49,126,128].…”
Section: Outcome 23 Progress Toward the Goal Is Constantly And Consistently Monitored And Reportedmentioning
confidence: 99%